Efectos del teatro infantil y su influencia en el desarrollo cognitivo en los estudiantes del primer grado del centro de educación básica “Carmen Yépez”, cantón ventanas, provincia de los ríos; propuesta de una guía didáctica - Miranda Vasconez, Irma Jesenia (2015)
The dramatic expression is part of life of every human being, is a language that uses the body as a medium, as an instrument of representation, expression, communication and creation. always be in balance between spontaneity and artistic technique, including the release of the self and knowledge of others. Dramatic expression to be of great importance for the development of the child, it can remain in the unconscious without being developed, which is necessary for the teacher starts to children / as early on in this area. We note with great regret that the Ecuadorian school system still has a vacuum by not providing all children the possibility of an aesthetic and social development through dramatic expression to lead them to an effective and innovative development deep. Schools do not take into account the dramatic expression as part of the cognitive development of the child / a so as to increase their potential for so meaningful learning. Expressive modalities manifest spontaneously in the game, children can give dramatically to events or activities that do not possess it, and improvise from various elements. Dramatic expression allows the child / to improvise space and mood patterns through mime, theater, linguistic expression, body language, musical language and dramatic play, making unlocking or disinhibition and spontaneity of gestures and movements